MARCHE DU TRAVAIL ET ACTIVITE FEMININE EN ALGERIE - Ghania BELOUCIF (Revue des Sciences Humaines, 2017)
This paper examines, though not in an exhaustive way, the part of women’s activity in the Algerian labour market. We have noted the considerable evolution of this activity in recent years. It has been evolving increasingly because of the structural mutations under way, the generalisation of compulsory access of females to education, the decrease of fertility rate and the fact that women have been noticeably forcing their way in the labour market to improve family income.